Clouston’s syndrome: a rare case report - Karjigi, Siddalingappa; Reddy, G. Aishwarya; Herakal, Kallappa C.; Reddy, Vedasree (International Journal of Research in Dermatology, 2020)
Ectodermal dysplasias are a heterogeneous group of disorders with primary defect in hair, teeth, nail and sweat glands with an estimated frequency of about seven per 10,000 births. Numerous types have been described and several classifications exist. Clouston’s syndrome (hidrotic ectodermal dysplasia) is a rare genodermatoses, characterized by a triad of nail dystrophy, alopecia and palmoplantar hyperkeratosis. Clouston’s syndrome is transmitted as an autosomal dominant trait and caused by mutations in the GJB6 gene (13q12), encoding the gap junction protein connexin 30 (CX30). At present, there is no treatment for the disease and management is purely supportive. The improved prognosis over time is likely due to greater recognition of the condition. In this report, a 23-year-old male patient with nail abnormalities and thickening of palmoplantar skin is reported. Anodontia of permanent dentition was present along with androgenic alopecia.